The rights of LGTBI people in Northern European countries: especially the right to gender reassignment - Santamaría Lambás, Fernando (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
The rights of LGTBI people are topical in 21st century society. It is our aim to study the regulations on sexual orientation and gender identity in Northern European countries (United Kingdom, Ireland, Iceland, Finland, Denmark, Norway, Sweden, Estonia, Latvia and Lithuania). We will focus on the extent to which the right to gender reassignment is recognised in national laws, and whether or not these laws respect the European Convention on Human Rights and European Union law, through the decisions of the Euro urt of Human Rights and the Court of Justice of the European Union.
Keywords: Europe; gender identity; sexual orientation; homosexual; transexual